2014
DOI: 10.2478/s11756-014-0377-5
|View full text |Cite
|
Sign up to set email alerts
|

The response of amphibian communities to fish and habitat features in Mediterranean permanent ponds

Abstract: Generalized linear models were used to test the effect of fish, using ponds with and without fish and habitat features as covariates, on richness and abundance of amphibian species. Five fish species and six amphibian species were recorded in 60 permanent ponds located in central Italy. The choice of covariates (macrophyte cover and pond surface area) was made after studying the correlations. The richness of amphibian species was not significantly affected by fish presence or macrophyte cover, in line with pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Along with the terrestrial habitat, aquatic microhabitats are essential environmental features to sustain newt populations. Field ecological studies have shown that amphibians, such as newts, are present in ponds with plentiful vegetation, which provides shelter for both adults and larvae, and substrate for spawning (Hartel et al, 2007;Joly, Miaud, Lehmann & Grolet, 2001;Landi, Piazzini & Saveri, 2014). In this study, we found that the availability of aquatic shelter allows half of the newt population (53%) to coexist with fish, whereas almost all newts (87%) left the water when they had no aquatic shelter.…”
Section: Impact Of Fish Presence On Habitat Use In Newtsmentioning
confidence: 58%
“…Along with the terrestrial habitat, aquatic microhabitats are essential environmental features to sustain newt populations. Field ecological studies have shown that amphibians, such as newts, are present in ponds with plentiful vegetation, which provides shelter for both adults and larvae, and substrate for spawning (Hartel et al, 2007;Joly, Miaud, Lehmann & Grolet, 2001;Landi, Piazzini & Saveri, 2014). In this study, we found that the availability of aquatic shelter allows half of the newt population (53%) to coexist with fish, whereas almost all newts (87%) left the water when they had no aquatic shelter.…”
Section: Impact Of Fish Presence On Habitat Use In Newtsmentioning
confidence: 58%
“…All our sampled wetlands, however, were larger than 0.5 ha, while the suggested optimal size for many amphibian species may be as small as 0.1 ha (Semlitsch et al, 2015; but see Bancila et al, 2017). Therefore, similarly to studies involving larger ponds (Landi et al, 2014;Porej & Hetherington, 2005), we may have failed to detect such a preference for the smallest wetlands as these were not available in our study area. Furthermore, as most wetlands had fish, probably because they were large enough not to dry out entirely or freeze, we may lack relevant variation in wetland size to detect the amphibian preference for smaller, fish-free wetlands.…”
Section: Amphibian Occurrence Patternsmentioning
confidence: 80%
“…In addition to competing with other fish such as Esox lucius, a native predator of higher commercial value [19,98], the bass has been reported to negatively affect amphibian species of conservation interest [131,207], representing an indirect source of economic loss. Indeed, some of the species affected by bass (e.g., the Italian crested newt Triturus carnifex; [131,141]) are not only important for nature tourism, but are also the subject of funded conservation and research programs, as they are particularly vulnerable to changes in both aquatic and terrestrial habitats [208].…”
Section: Socio-economic Implications Of Bass Introductionsmentioning
confidence: 99%